Sepsis-Associated Encephalopathy: A Mini-Review of Inflammation in the Brain and Body - Ito, Hiroshi; Hosomi, Sanae; Koyama, Yoshihisa; Matsumoto, Hisatake; Imamura, Yukio; Ogura, Hiroshi; Oda, Jun (Frontiers in Aging Neuroscience, 2022)
Sepsis is defined as a life-threatening multi-organ dysfunction triggered by an uncontrolled host response to infectious disease. Systemic inflammation elicited by sepsis can cause acute cerebral dysfunction, characterized by delirium, coma, and cognitive dysfunction, known as septic encephalopathy. Recent evidence has reported the underlying mechanisms of sepsis. However, reasons for development of inflammation and degeneration in some brain regions and persistence of neuroinflammation remain unclear. This mini-review describes the pathophysiology of region-specific inflammation after sepsis-associated encephalopathy (SAE), clinical features, and future prospects for treatment of SAE. The hippocampus is highly susceptible to inflammation, and studies of treatment with antibodies to cytokine receptors, such as interleukin-1β, are in progress. Future development of clinically applicable therapies is expected.